2020
DOI: 10.1080/22221751.2020.1825016
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of two chemiluminescence and three lateral flow immunoassays for the diagnosis of COVID-19 and assessment of antibody dynamic responses to SARS-CoV-2 in Taiwan

Abstract: This multicenter, retrospective study included 346 serum samples from 74 patients with coronavirus disease 2019 (COVID-19) and 194 serum samples from non-COVID-19 patients to evaluate the performance of five anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody tests, i.e. two chemiluminescence immunoassays (CLIAs): Roche Elecsys® Anti-SARS-CoV-2 Test (Roche Test) and Abbott SARS-CoV-2 IgG (Abbott Test), and three lateral flow immunoassays (LFIAs): Wondfo SARS-CoV-2 Antibody Test (Wondfo T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 34 publications
3
41
0
1
Order By: Relevance
“…We demonstrate that antibodies against 2 main structural proteins (S and N) of SARS-CoV-2 in patients with asymptomatic or mild infections were almost undetectable within the first week after diagnosis. Antibodies rapidly increased in subsequent weeks and peaked around weeks 4–7 before declining during the later phase of infection, consistent with previously reported findings ( 2 , 5 7 ). However, few studies have reported the persistence of long-term humoral immune response to SARS-CoV-2 up to 18–30 weeks after diagnosis ( 5 ), especially among mildly symptomatic or asymptomatic infected patients.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…We demonstrate that antibodies against 2 main structural proteins (S and N) of SARS-CoV-2 in patients with asymptomatic or mild infections were almost undetectable within the first week after diagnosis. Antibodies rapidly increased in subsequent weeks and peaked around weeks 4–7 before declining during the later phase of infection, consistent with previously reported findings ( 2 , 5 7 ). However, few studies have reported the persistence of long-term humoral immune response to SARS-CoV-2 up to 18–30 weeks after diagnosis ( 5 ), especially among mildly symptomatic or asymptomatic infected patients.…”
supporting
confidence: 92%
“…We measured antibodies against 2 main immunogens of SARS-CoV-2, the nucleocapsid (N) and spike (S) proteins, by using 2 well-validated sensitive and specific serologic assays, Elecsys Anti–SARS-CoV-2 assay (Roche, https://diagnostics.roche.com ) ( 2 ) and SARS-CoV-2 Surrogate Virus Neutralization Test (sVNT) (GenScript, https://www.genscript.com ) ( 3 ). The former is an electrochemiluminescence immunoassay that uses recombinant N protein for qualitative detection of pan Ig, including IgG, against SARS-CoV-2.…”
mentioning
confidence: 99%
“…It has been shown in several studies that most SARS-CoV-2 antibody assays exhibit variable performance during the early phases infection, but the concordance improves after day 14 of symptoms onset where IgG seroconversion rate reaches 90% [ 12 , 40 , 41 ]. According to recent data on COVID-19 serology testing, the performance of serological tests was found to stabilize ≥21 days after symptom onset [ 42 ]. Moreover, previous studies have shown that convalescent COVID-19 patients have higher neutralization activity [ 40 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy to mention that the variation in sensitivity values reported in most studies on the currently available commercial automated analyzers, could be in part due to the variation in the time of sample collection. The sensitivity of serological tests is usually lower at early stages of infection (<7 days), and the performance starts to stabilize ≥ 21 days after symptom onset [ 8 , 42 ]. In correlation to the sVNT, LIAISON ® XL had a 92.2% positive percent agreement and 100% negative percent agreement ( Table 4 ), this is in concordance with another study reporting positive and negative percent agreements of 94.4% and 97.8%, respectively, for LIAISON ® XL using MNT as reference method [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…These rapid assays provide a low-throughput antibody testing option for laboratories with limited resources and are particularly useful for epidemiologic field studies. However, a meta-analysis evaluating the diagnostic accuracy of SARS-CoV-2 serologic testing concluded that LFIAs were consistently less sensitive than ELISA or CLIA methods [ 9 ], and subsequent studies have reported a wide range of sensitivities and specificities [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. Nevertheless, the Infectious Diseases Society of America (IDSA) recommends against the use of IgG or IgM antibody combination tests, where detecting either antibody isotype is used to define a positive result [ 7 ].…”
Section: Introductionmentioning
confidence: 99%